2022
DOI: 10.1126/science.abf7470
|View full text |Cite
|
Sign up to set email alerts
|

Marginal zone B cells acquire dendritic cell functions by trogocytosis

Abstract: Marginal zone (MZ) B cells produce broad-spectrum antibodies that protect against infection early in life. In some instances, antibody production requires MZ B cells to display pathogen antigens bound to major histocompatibility complex class II (MHC II) molecules to T cells. We describe the trogocytic acquisition of these molecules from conventional dendritic cells (cDCs). Complement component 3 (C3) binds to murine and human MHC II on cDCs. MZ B cells recognize C3 with complement receptor 2 (CR2) and trogocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 46 publications
1
33
0
Order By: Relevance
“…Although trogocytosis or cell fusion can be mistaken as transdifferentiation 27 , 28 , we show that it only accounts for a very minor fraction of B-MF. Instead, the overwhelming majority of B-MF derived from highly FACS-purified CD45.2 + B-cell precursors of the B-cell lineage tracer Mb1-EYFP + mice only expressed CD45.2 after in vitro co-differentiation with CD45.1 + monocyte/macrophages or adoptive transfer in tumor-bearing CD45.1 + mice.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Although trogocytosis or cell fusion can be mistaken as transdifferentiation 27 , 28 , we show that it only accounts for a very minor fraction of B-MF. Instead, the overwhelming majority of B-MF derived from highly FACS-purified CD45.2 + B-cell precursors of the B-cell lineage tracer Mb1-EYFP + mice only expressed CD45.2 after in vitro co-differentiation with CD45.1 + monocyte/macrophages or adoptive transfer in tumor-bearing CD45.1 + mice.…”
Section: Discussionmentioning
confidence: 75%
“…Because B-MF could be misinterpreted as trogocytosis or cell fusion 27 , 28 , we performed a series of B-cell differentiation experiments using highly FACS-purified CD19 + B220 + B cells (Lin − , >99% purity, Supplementary Fig. 3a ) from BM of naïve mice.…”
Section: Resultsmentioning
confidence: 99%
“…Such organisms also contain T celldependent Ags, and MZB cells can generate Ab responses to them as well, following interaction with T follicular helper or NKT cells. A recent study showed that MZB cells can capture peptideMHC class II complexes from DCs, in a manner that involves binding of complement component C3 with peptideclass II complexes on DCs, followed by plasma membrane transfer to MZB cells via complement receptor 2 in a process called trogocytosis, thus endowing MZB cells with DC-like functions (56). The capacity of MZB cells to generate memory responses remains uncertain.…”
Section: Innate-like B Cellsmentioning
confidence: 99%
“…A 2022 report by Schriek et al [11 ▪▪ ] uncovered a novel complement-dependent process that facilitates antigen presentation by marginal zone B cells (MZB) to CD4 + T cells. C3b activation occurs preferentially on glycosylated sites on class II MHC molecules expressed by conventional dendritic cells (cDC), resulting in C3dg opsonization.…”
Section: Complement and B Cellsmentioning
confidence: 99%